Trade Openness Reduces Volatility When Countries Are Well Diversied - Haddad, Mona E.; Lim, Jamus Jerome; Saborowski, Christian (2012)
This paper addresses the mechanisms by which trade openness affects growth volatility. Using a diverse set of export diversification indicators, it presents strong evidence pointing to an important role for export diversification in reducing the effect of trade openness on growth volatility. The authors also identify positive thresholds for product diversification at which the effect of openness on volatility changes sign. The effect is shown to be positive only for a minority of countries with highly concentrated export baskets. This result is shown to be robust to both explicit accounting for endogeneity as well as the inclusion of a host of additional controls.